FROM TERRORISTS TO PEACE WARRIORS: Mentoring Poso Islamic Jihadists Using The Heart, Hand, and Head Approach - Thahir, Lukman (Hunafa: Jurnal Studia Islamika, 2022)
This article is the result of the author’s qualitative research on the Poso terrorist prisoner community for six months in prison and one year outside of prison with Heart, Hand and Head approach. The objectives are: First, to change the mindset of the Poso jihadist community from terrorists to peace warriors. Second, to formulate the concept of terrorist mentoring with the Heart, Hand, and Head approach. The main questions of this research were focused on: 1). How were profile and the pattern of mentoring with the Heart, Hand and Head approach for the ex-jihadist Poso?, and 2). What activities did the former Poso jihadists do as Peace Warriors ?. To answer this problem, the methods used: 1). Phenomenological Descriptive, 2). Bloom’s Taxonomy and Social Pedagogic Learning Method; and 3). Mentoring Guide from the Center for Health Leadership & Practice Public Health Institute Oakland. Data collection techniques employed were observation, in-depth interview and documentation. The results show that 1). The profile of the ex-Poso jihadists are: the executor of the Tentena bombing, the mutilation of five Christian high school students, the shooting coordinator of Pastor Susianti. Then, The pattern of mentoring is divided into two parts: in prison, due to time constraints, it emphasizes the aspects of building trust and winning sympathy (Heart), outside of prison, the three approaches of Heart, Hand and Head are carried out in a holistic and integrative manner. 2). There are three activities carried out by former Poso jihadists as peace warriors: First, becoming a speaker for counter terrorism activities. Second, to be part of the deradicalization process of the East Indonesian Mujahidin group. Third, attracting ten former Poso terrorists to join the peace warriors.